2014
DOI: 10.1155/2014/176597
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Allergic Rhinitis with Ectoine Containing Nasal Spray and Eye Drops in Comparison with Azelastine Containing Nasal Spray and Eye Drops or with Cromoglycic Acid Containing Nasal Spray

Abstract: Objectives. Allergic rhinitis is a common disease with increasing prevalence and high impact on economic burden and comorbidities. As treatment with pharmacological drugs is not always satisfactory due to side effects and incomplete efficacy, alternative treatment strategies are needed. Ectoine is an osmolyte with membrane stabilizing and inflammation reducing capacities. Nasal spray and eye drops containing ectoine are promising new treatment regimens for allergic rhinitis sufferers. Design and Methods. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 23 publications
(18 reference statements)
1
40
0
2
Order By: Relevance
“…Its current sales price is approximately US$1000 kg −1 , making ectoine a high‐priced product . The applications of ectoine are manifold and include skin preservation, skin protection against cell damage and aging, and the treatment of diseases such as atopic dermatitis, lung inflammation, allergic rhinitis, and Alzheimer's disease . Furthermore, ectoine is used as a medium ingredient to enhance biotechnology processes …”
Section: Introductionmentioning
confidence: 99%
“…Its current sales price is approximately US$1000 kg −1 , making ectoine a high‐priced product . The applications of ectoine are manifold and include skin preservation, skin protection against cell damage and aging, and the treatment of diseases such as atopic dermatitis, lung inflammation, allergic rhinitis, and Alzheimer's disease . Furthermore, ectoine is used as a medium ingredient to enhance biotechnology processes …”
Section: Introductionmentioning
confidence: 99%
“…In this NIS, we observed a statistically significant improvement in nasal symptoms of 27% in the ATANS group, demonstrating a similar effectiveness of ATANS to the aforementioned non-pharmacological treatment options. In another NIS, ectoine-containing nasal spray and eye drops seemed to be a comparable alternative to traditional anti-inflammatory agents such as azelastine, cromoglycin and levocabastine for the treatment of AR [26,27]. Patients using ectoine nasal spray showed an improvement of about 32% in the symptoms of rhinorrhoea and 30% in nasal obstruction [26], as well as a reduction of 23% in the total nasal symptom score [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that products containing ectoine may be a better alternative to other products, as they reduce ocular and nasal symptoms with no side effects (40)(41)(42). Promising effects such as reduction of nasal airway obstruction and crust formation were also observed in patients with rhinitis sicca anterior treated with nasal spray containing ectoine alone or in combination with dexpanthenol (43).…”
Section: Alleviation Of Inflammatory Reactionmentioning
confidence: 99%